Changes in the occurrence of safe haven assets after Russian aggression on Ukraine - Karolina Siemaszkiewicz (Scientific Journal of Bielsko-Biala School of Finance and Law, 2024)
Two years ago, on 24 February 2022, Russia launched a multi-front attack against Ukraine, which was the largest military action against a European country since World War II. The aim of this paper is to compare the performance of safe haven assets after Russian aggression on Ukraine. We investigate the dynamic relationship between the countries: France, Germany, Great Britain, Japan, Poland, and the United States of America, and popular instruments: gold, silver, natural gas, crude oil, U.S. dollar (or Euro), Swiss franc, and Bitcoin. By choosing different countries we want to compare the influence of Russian aggression in Ukraine on the various market economies. We considered the period after Russian aggression in Ukraine, to be from 01.02.2022 – 01.03.2024. We estimate the parameters of DCC or CCC models to compare the dynamic relationship between the above-mentioned stock markets and financial instruments. The result shows that mostly, natural gas can be considered as a safe haven instrument during that time sample. For investors from Germany, Great Britain, and the USA we can observe that four out of seven instruments were able to act like safe haven assets. Surprisingly, only Bitcoin was not identified as a safe haven instrument for any country.